Sri Lanka Report on the Observance of Standards and Codes : Accounting and Auditing Update - World Bank Group (World Bank, Washington, DC, 2015)
The Report on the Observance of Standards and Codes, Accounting and Auditing (ROSC AA) in Sri Lanka aims to assess the progress made on implementation of the policy recommendations of the first ROSC AA in 2004 and supports the Government of Sri Lanka in preparing a country action plan. This will further enhance the quality of corporate financial reporting, and thereby contribute toward the country’s goal of improving the investment climate, attracting foreign direct investment (FDI), and fostering business development. The ROSC review, requested by the Minister of Finance and Planning, entailed an evaluation exercise that assesses the strengths and weaknesses of existing institutional frameworks that underpin financial accounting and auditing practices; determines the comparability of national accounting and auditing standards; and evaluates the effectiveness of enforcement mechanisms for ensuring compliance with existing national standards, rules, and regulations. The review was conducted from December 2013 to September 2014 using the World Bank’s multi-layered review methodology. All findings reflect this time period of the review; some stated future events may have been achieved by publication date. The data and information used for the review was gathered from a diagnostic questionnaire completed by stakeholders; by reviewing accountancy profession-related documents; and through interviews with many stakeholders from government, regulatory and accountancy bodies, accounting and auditing firms, banks, insurance companies, state-owned enterprises (SOEs), small and medium-size enterprises (SMEs), and academia. The review focused on assessing the institutional framework underpinning accounting and auditing practices in the private sector and in SOEs of the country in comparison with international standards and good practice.